2015
DOI: 10.1097/dcr.0000000000000379
|View full text |Cite
|
Sign up to set email alerts
|

Chlorhexidine With Isopropyl Alcohol Versus Iodine Povacrylex With Isopropyl Alcohol and Alcohol- Versus Nonalcohol-Based Skin Preparations

Abstract: The use of 2.0% chlorhexidine with 70.0% isopropyl alcohol versus 0.7% iodine povacrylex with 74.0% isopropyl alcohol or alcohol-based versus nonalcohol-based skin preparations does not significantly influence the incidence of surgical site infections or readmission within 30 days for surgical site infection after clean-contaminated colorectal operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Some evidence suggests that chlorhexidine-based preparations are more effective, 16,17 other reviews are less conclusive. 18,19 The new protocol harnesses both mechanisms through their combined use. Chlorhexidine is used for the initial skin preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence suggests that chlorhexidine-based preparations are more effective, 16,17 other reviews are less conclusive. 18,19 The new protocol harnesses both mechanisms through their combined use. Chlorhexidine is used for the initial skin preparation.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies showed no significant difference between the tested antiseptics. It is difficult to compare these studies because variable antiseptics and concentrations were used.…”
Section: Preoperative Measuresmentioning
confidence: 99%
“…A retrospective propensity-adjusted comparison of colorectal surgery performed in the state of Michigan revealed no difference in the rate of SSI when comparing chlorhexidine-alcohol-based to PI-alcohol-based solutions. 12 Likewise, they found no difference in a larger comparison on colorectal surgery comparing alcohol-based to aqueous-based solutions. A more recent noninferiority randomized trial comparing PI-alcohol to chlorhexidine-alcohol failed to show noninferiority of the PI-alcohol solution.…”
Section: Discussionmentioning
confidence: 99%